2019
DOI: 10.1039/c9ra05024h
|View full text |Cite
|
Sign up to set email alerts
|

VOX supported on TiO2–Ce0.9Zr0.1O2 core–shell structure catalyst for NH3-SCR of NO

Abstract: VOX/TiO2–Ce0.9Zr0.1O2 catalyst exhibits high activity and selectivity in a wide temperature window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 55 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…3(ad) that Ti-C,N has little effect on the crystallite size (about 13 nm), and the displayed fringe spacing is 0.352 nm, which corresponds to the (101) plane of anatase TiO 2 , indicating that C,N modification does not change the crystal phase of TiO 2. 31 It can be seen from Fig. 3(e-h) that the doping of active components has a great influence on the crystallite size; in particular, CoO z doping can improve the crystallite size (about 20 nm), but there are no lattice fringes on the catalyst surface caused by MnO x /CeO y /CoO z .…”
Section: Tem Analysismentioning
confidence: 93%
“…3(ad) that Ti-C,N has little effect on the crystallite size (about 13 nm), and the displayed fringe spacing is 0.352 nm, which corresponds to the (101) plane of anatase TiO 2 , indicating that C,N modification does not change the crystal phase of TiO 2. 31 It can be seen from Fig. 3(e-h) that the doping of active components has a great influence on the crystallite size; in particular, CoO z doping can improve the crystallite size (about 20 nm), but there are no lattice fringes on the catalyst surface caused by MnO x /CeO y /CoO z .…”
Section: Tem Analysismentioning
confidence: 93%
“…34 The literature was reported that there was only Lewis acid sites over the anatase (TiO 2 ). 32,33,35 Therefore, the intensity of the band of the Lewis acid sites over CuAl-LDO/TiO 2 NTs catalyst was stronger than CuAl-LDO catalyst. In addition, compared with CuAl-LDO, CuAl-LDO/TiO 2 NTs catalyst have the most abundant and strongest acid sites over the surface, which was in good agreement with their NH 3 -TPD results.…”
Section: Sem and Eds-mapping Analysismentioning
confidence: 98%
“…The bands located at $1440 cm À1 , $1540 cm À1 , 1590 cm À1 and 1655 cm À1 were corresponded to the Lewis acid sites ($1440 cm À1 and 1590 cm À1 ) and Brønsted acid sites ($1540 cm À1 and 1655 cm À1 ), respectively. 32,33 The bands around 1485 cm À1 were assigned to both Brønsted and Lewis acid sites over catalysts. 34 The literature was reported that there was only Lewis acid sites over the anatase (TiO 2 ).…”
Section: Sem and Eds-mapping Analysismentioning
confidence: 99%